2015
DOI: 10.3390/molecules200712300
|View full text |Cite
|
Sign up to set email alerts
|

Heterocycles 38. Biocatalytic Synthesis of New Heterocyclic Mannich Bases and Derivatives

Abstract: This paper describes the biocatalytic synthesis of new Mannich bases containing various heterocyclic rings (thiazole, furane, thiophene, pyridine) by applying the lipase catalyzed trimolecular condensation of the corresponding heterocyclic aldehydes with acetone and primary aromatic amines, in mild and eco-friendly reaction conditions. The obtained Mannich bases were acylated to their corresponding N-acetyl derivatives. All compounds were characterized by 1 H-NMR, 13 C-NMR and MS spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The catalytic activity of lipase from Candida antarctica lipase B (CAL-B) in Mannich reactions was studied by the group of Zaharia, who showed that this enzyme was very effective in the synthesis of new Mannich bases derived from 2-phenylthiazole and 2-phenylaminothiazole ( Scheme 15 ). While the reaction worked well with acetone as the nucleophile component, affording the target compounds with good yields in mild and ecofriendly reaction conditions, this enzyme proved inactive with other ketones [ 76 , 77 ].…”
Section: The Mannich Reactionmentioning
confidence: 99%
“…The catalytic activity of lipase from Candida antarctica lipase B (CAL-B) in Mannich reactions was studied by the group of Zaharia, who showed that this enzyme was very effective in the synthesis of new Mannich bases derived from 2-phenylthiazole and 2-phenylaminothiazole ( Scheme 15 ). While the reaction worked well with acetone as the nucleophile component, affording the target compounds with good yields in mild and ecofriendly reaction conditions, this enzyme proved inactive with other ketones [ 76 , 77 ].…”
Section: The Mannich Reactionmentioning
confidence: 99%
“…Leonte et al [58] described the biocatalytic synthesis of new Mannich bases containing various heterocyclic rings (thiazole, furane, thiophene, pyridine) by applying the lipase catalyzed trimolecular condensation of the corresponding heterocyclic aldehydes (50) with acetone (52) and primary aromatic amines (51) in mild and eco-friendly reaction conditions (Scheme-XV). Penicillin acylase isolated from E. coli hydrolyzes the different forms of penicillin such as penicillin G (58) into 6-aminopenicillinic acid (6-APA) (…”
Section: Scheme-v: Epoxidation Using Cytochrome P450 Enzymementioning
confidence: 99%
“…8−16 Amidation of aniline and formation of a Mannich base was carried out using lipase as a catalyst. 13,14 To explore the complete potential, the promiscuous nature of lipase can be explored by varying the source of lipase-producing bacteria or fungi. 1−3 This makes lipase a suitable catalyst for the synthesis of a range of chemicals.…”
Section: Introductionmentioning
confidence: 99%